Legal Compliance with Merger Notification Requirements for Foreign Business Entities in the Crypto Asset Sector: An Analysis of KPPU Decision No. 16/KPPU-M/2024 - Melki T. Tunggati; Karlin Z. Mamu; Sofyan Piyo (Syura: Journal of Law, 2026)
This research critically examines the legal compliance of foreign business actors with merger notification obligations in Indonesia's crypto asset sector, using KPPU Decision Number 16/KPPU-M/2024 as its empirical anchor while offering a theoretical contribution that integrates extraterritorial jurisdiction doctrine with legal compliance theory. Employing normative legal research through statutory, case, and comparative approaches, this study evaluates the reasoning quality of the Commission's decision rather than merely describing it, finding that while two of four violation elements were soundly proven, two others were established declaratively without transparent methodology. A comprehensive four-country comparison (Indonesia, the European Union, the United States, and Singapore) reveals that Indonesia is the only jurisdiction lacking any structured compliance guidance for foreign investors, and that its fixed administrative sanction produced a disproportionately weak deterrent against a multinational entity affiliated with Binance. The study further develops an original analytical framework identifying four structural dimensions unique to crypto markets, namely market concentration, network effects, platform dominance, and data concentration, none of which are captured by Indonesia's conventional asset-and-sales-value merger thresholds. These findings indicate that foreign business actors' non-compliance stems not merely from individual negligence but from systemic regulatory and institutional gaps. The research concludes that effective merger oversight in the crypto sector requires responsive regulatory reform, a gradual transition toward pre-merger notification, and sector-specific compliance instruments, while acknowledging its limitation as a single-case normative study whose findings warrant further empirical validation.